Human Resources Performance Measurement Approaches Compared to Measures Used in Master’s Theses in ASU - Aldulaimi, Saeed Hameed; Obeidat, Mohammad Abdul Qadir (International Review of Management and Marketing, 2016)
The purpose of this paper is to identify the required factors that can be considered necessary in conceptualizing the features of HR performance measurement system appropriate in the modern organizational setting. This study raises this question: what is the reality of current research in measuring HR performance in ASU compared to the measures used in literature of HR studies? The paper uses a systematic approach in reviewing and examining existing HR measures used in Master’s theses in ASU in comparison with the measures developed in literature, consequently tracing process has been made to the researches that focused on the HR performance from 2011 to 2015. Furthermore, citation analysis was used to gather the well-known models in measuring HR performance, and summarize the variables or dimensions utilized for this purpose. The outcomes of this review contribute to and update existing literature on HR measures in two ways: identification of gaps in terms of practical usefulness and academic research, suggestions of solutions in the form of a conceptual framework to improve measurement and HR performance measurement using the correct variables, and recommendation of a direction for future research with regard to using the right variables based on research theory and purpose. This study targeted one university to discover the use of methods to measure HR performance. This study has several implications: it underscores the critical academic role in enhancing HR performance measures in research and professional. HR performance measurement should be aligned with valid theories and practices. To assist researchers to look at most of the models related to HR performance measurement tools gathered in one study and choose the applicable one which lead to achieve the research objectives. This is a seminar paper that defines the measuring attributes of HR performance for the conceptualization of a workable framework of the features of HR. Keywords: Human Recourse, Human Recourse Performance, Measurement. JEL Classifications: J25, O15